A Cross-Sectional Study on Pregnant Women's Knowledge and Chronic Energy Deficiency (CED) in Bandar Lampung City - Monica Dara Delia Suja; Indah Budiarti; Lely Sulistianingrum (Tadulako University, 2026)
Pregnant women who suffer from chronic energy deficiency (CED) tend to give birth to low birth weight babies. Based on data from the 2022 Lampung Province Health Profile, there were 5,142 pregnant women with CED. This study aims to examine the relationship between maternal knowledge and the incidence Chronic Energy Deficiency (CED) in pregnant women in Bandar Lampung City. This cross sectional study conducted on August 2025 in 5 community health centers with the highest number of pregnant women with CED in Bandar Lampung, namely Panjang, Kedaton, Kemiling, Kupang Kota, and Rajabasa Community Health Centers. Population in this study consisted of all pregnant women in the five health center areas where the study was conducted. Sample size was calculated using the Slovin formula with a population of 384 people in the five areas, resulting in a sample size of 200 pregnant women, which will be divided into five areas with a minimum sample of 40 respondents in each health center area. Data collection was carried out by filling out questionnaires distributed directly to mothers when they came to the health center or Posyandu. Variables was mothers' knowledge about the causes of CED and the incidence of CED in pregnant women. Analysis was performed using the chi-square statistical test and logistic regression. The results show that there is a relationship between mother’s knowledge dan CED (p-value <0,05). Educational programs on the causes of chronic energy deficiency and counseling on ANC are required to increase mothers' knowledge and prevent CED.